Cenários participativos e governança no entorno do Parque Estadual do Rio Doce: o papel dos sistemas agroflorestais como estratégia de desenvolvimento - Luiz Gustavo de Souza Paula (2019)
Reconciling economic interests and biodiversity conservation in the buffer areas of protected areas is a major challenge. This study explores participatory scenarios and spatially explicit modeling as a way to forge innovative public policies and governance framework in the buffer area of Rio Doce State Park, Minas Gerais, Brazil. Throughout the work, four methodological approaches were used: participatory scenarios for exploring possible and desirable futures, as seen by the local community, for the year 2050; multicriteria analysis for modeling and mapping of areas with biophysical potential to develop Agroforestry Systems (SAFs); development of a framework of governance measures aimed at the local socio-environmental development in order to implement community activities in places where there is biophysical potential. Finally was carried out a qualitative evaluation of the current project based on the concepts of efficiency, effectiveness and effectiveness. The results show that the community wants socioeconomic growth coupled with environmental preservation activities and agricultural production based on SAFs. In parallel, a spatially explicit model identified areas with biophysical potential for the implementation of SAFs. The multicriteria analysis showed that 0.12% of the area of the municipality of Pingo d ' Água has high potential for SAFs (8 ha). Our results also show the Framework of Social and Environmental Governance Measures capable of implementing SAFs among other activities with the potential to enhance local development around the Rio Doce state park and indicate which actors may be potential enablers of these initiatives. Finally, the evaluation of the project highlights the need for improvements, mainly in relation to aspects related to the effectiveness of the project. This work contributes to systematize and discussing the challenges embedded in reconciling development and conservation around protected areas in the context of Pingo d´’Agua municipality. The scientific importance of this work lies on putting togeher a four step methodology able to integrate local and scientific knowledge about land use change that can be replicated to other buffer of protected areas that need to reconcile econommic growth and biodiversity issues.